Synthesis and characterization of new D-π-D type Schiff base ligands and its complexes with Cobalt(II), Ruthenium(II) - Erden, Ibrahim; Demirhan, Nebahat; Avcata, Ulvi (MAIK NAUKA/INTERPERIODICA/SPRINGER, 2010)
A Schiff base ligands, N-{(1E,2E)-3-[4-(dimethylamino)phenyl]prop-2-en-1-ylidene}-1,10-phenanthrolin-5-amine(mpa) and (1E,2E)-3-[4-(dimethylamino)phenyl]acrylaldehyde9H-fluoren-9-ylidenehydrazone(mfh), have been synthesized from the reaction of 4,5-diazafluorenone-9-hydrazone and 5-amino-1,10-phenanthroline with 4-(dimethylamino)cinnamaldehyde. The Co(II) and Ru(II) complexes of the ligands were prepared and characterized. The metal-to-ligand ratio of the Co(II) complex was found to be 2: 1 and that of the Ru(II) complex was found to be 1: 1. The ligands and complexes have been characterized by FTIR, UV-visible, H-1 NMR and fluorescence spectra, as well as, elemental analyses, TGA-DSC-DTG and mass spectra.
Keywords: NICKEL(II); BINUCLEAR; Chemistry